Androgenetic Alopecia: Relationship to Anthropometric Indices, Blood Pressure and Life-Style Habits - Danesh-Shakiba M; Poorolajal J; Alirezaei P (Dove Medical Press, 2020)
Mohammad Danesh-Shakiba,1 Jalal Poorolajal,2,3 Pedram Alirezaei4 1School of Medicine, Hamadan University of Medical Sciences, Hamadan, Iran; 2Department of Epidemiology, School of Public Health, Hamadan University of Medical Sciences, Hamadan, Iran; 3Modeling of Noncommunicable Diseases Research Center, Hamadan University of Medical Sciences, Hamadan, Iran; 4Psoriasis Research Center, Hamadan University of Medical Sciences, Hamadan, IranCorrespondence: Pedram AlirezaeiPsoriasis Research Center, Department of Dermatology, Farshchian Hospital, Mirzadeh Eshghi Street, Hamadan 6517838678, IranTel +98 81 3821 868Fax +98 8138381591Email prc@umsha.ac.irPurpose: The association of androgenetic alopecia (AGA) with cardiovascular risk factors including hypertension, smoking and high body mass index (BMI) has been investigated in several studies. However, the results are discrepant. The aim of the present study was to evaluate the association of AGA with anthropometrics, blood pressure and lifestyle habits.Patients and Methods: In this case-control study, 256 men with AGA and 256 age-matched healthy controls were evaluated. Systolic and diastolic blood pressures, as well as anthropometric indices were measured. Data on lifestyle habits including smoking, hookah use and alcohol consumption were also collected.Results: Patients with AGA had significantly lower BMI and lower waist to hip ratio as compared to controls (p = 0.012 and p = 0.002, respectively). Other anthropometrics as well as mean systolic and diastolic blood pressures were not significantly different between the two groups. There was no significant difference between patients and controls in terms of lifestyle habits. Patients with severe AGA (Norwood-Hamilton classification type IV-VII) had significantly higher systolic and diastolic blood pressures as compared to those with mild to moderate AGA (Norwood-Hamilton classification type II, III), but the mean age of the former group was also significantly higher (p < 0.001).Conclusion: In contrast to some previous studies, our findings did not show a significant association between certain cardiovascular risk factors (such as hypertension and smoking) and AGA. Although lower BMI and lower waist to hip ratio were observed in the patient group, these values were within normal limits and therefore not biologically significant.Keywords: androgenetic alopecia, anthropometric, blood pressure, life style, smoking